Baseline Assessment of Proposals to Revise Federal Environmental Licensing in Brazil : A Contribution to Discussions - World Bank (Washington, DC, 2017)
In order to enrich discussions on improving federal environmental licensing, this study covers a baseline of other studies and research done in recent years, to bring out key challenges arising in the various stages of the licensing process, as well as several bills of law recently presented in the Brazilian National Congress. The global social, political, economic, and institutional context raises many challenges and new opportunities. The World Bank has therefore revised and approved new social and environmental standards, to come into effect in January, 2018. Improving environmental licensing in Brazil is thus a timely initiative, as the entire world seeks consistence and coherence for sustainable social and environmental policies, along with stronger institutions and strategic planning to mitigate potential socio-environmental impacts. There is a clear need for a more rational regulatory environment, based on a complex but minimally coherent set of norms. This discussion is essential, since licensees need a minimum of legal certainty regarding the risks they face, while society cannot be left at the mercy of economic development, with no reasonable protection of the environment.